RESPON PERTUMBUHAN BIBIT KAKAO ( Theobroma cacao L.) TERHADAP PEMBERIAN PUPUK KANDANG KAMBING DAN PUPUK ORGANIK CAIR (POC) - Usrin Usrin; Djoko Heru Pamungkas; Sri Widata (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to determine the effect of the combination of goat fertilizer and Liquid Organic Fertilizer (POC) from goat manure on the response of the best growth of cacao (Thebroma cacao L.) seeds. The research is a field experiment compiled in a Randomized Complete Group Design (RAKL). The study was conducted at the Nglanggeran Agricultural Technology Park (TTP) from April to July 2018. The treatment consisted of 4 combinations and 1 dick, namely: Provision of goat manure with a ratio of 1: 1, goat manure with a ratio of 1: 2 and fertilizer application liquid organic with a ratio (0.75) equivalent to 10 L / ha, the distribution of liquid organic fertilizer with a ratio (1.5) equivalent to 20 L / ha and control treatment. (Observations include plant height, leaf number, leaf length, leaf width, stem diameter, fresh weight and plant dry weight). Observation data were analyzed with variance at 5% real level. Differences between treatments were tested by the DMRT Multiple Range Test at a 5% level. Based on the results of the study, the effect of the combination of goat manure and liquid organic fertilizer showed no significant difference (no interaction) with all nursery observation variables. The results of the response of the administration of goat manure did not occur significantly to any variable of nursery observation. The administration of liquid organic fertilizers did not occur in a significant difference to the variables of nursery observation. The treatment of liquid organic fertilizer was not significantly different from the control